'The right not to have anything': the 'Nasreddin in Russia' newspaper. Issue 2 (4th May 2019) - Abdulaev, Narmina
ABSTRACT: The Nasreddin in Russia newspaper is part of an initiative undertaken by migrant workers along with a group of local artists in St. Petersburg, Russia. It serves as an alternative platform from which the voices of the migrant workers, often silenced in the traditional media, may be heard. Most of the research dealing with migrant workers in Russia focuses on the legal and political aspects of the issue. The present article is a qualitative study that analyzes the contents of four issues of the newspaper. The article uses thematic analysis and discourse analysis to identify and interpret the main matters of concern raised in the Nasreddin in Russia newspaper.